GAP ANALYSIS AND SANITARY LANDFILL DEVELOPMENT STRATEGY FOR COT PADANG NILA LANDFILL, PIDIE REGENCY - Yusmar, Arief Maulana; Arief Rahman; Lisa Ginayatri (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Population growth and expanding socio-economic activities have significantly increased municipal solid waste (MSW) generation in Pidie Regency, Aceh Province, Indonesia. The Cot Padang Nila Final Disposal Site, the sole landfill facility serving the regency, currently processes approximately 45 tonnes of waste per day under an open dumping system. This study aims to quantify current and projected MSW generation over a 20-year planning horizon (2025–2045) and formulate a comprehensive and technically grounded optimization strategy. A quantitative evaluative research design was employed, integrating systematic field observations, institutional document analysis. Total MSW generation is projected to increase from approximately 317 tonnes/day in 2024 to 368 tonnes/day by 2045. The proposed optimization framework encompasses a transition to a cell-based sanitary landfill system with engineered composite liner, multi-stage leachate treatment, structured methane gas recovery, an aerobic composting facility (capacity: 128 t/day), a Material Recovery Facility (MRF) for inorganic fractions, and a comprehensive fleet depot. Implementation of these measures is projected to substantially improve waste management effectiveness, reduce environmental contamination risks, and extend the operational service life of the landfill.